Hubungan Sedentary Lifestyle dan Kebiasaan Makan dengan Status Gizi Ibu Rumah Tangga di Wilayah Kerja Puskesmas Manyaran Semarang - Meilia Winarti Handayani; Eko Farida (Media Gizi Kesmas, 2024)
Background: Overnutrition and obesity in adults from 2007 to 2018 has increased by 8.8% to 13.6% for overnutrition and 10.3% to 21.8% for obesity. Semarang City has an adult female obesity prevalence of 29.9%. Housewives are more at risk of obesity than working mothers. Some of the factors that cause housewives to become obese are sedentary lifestyle, less of do physical activity, dietary intake, and consumption of unhealthy intake. Objectives: To know the relationship between sedentary lifestyle and eating habits in terms of energy intake, protein intake, fat intake and carbohydrate intake with the nutritional status of housewives. Methods: This typed of research used quantitative methods with a case control study design. The sample of this study amounted to 41 case samples and 41 control samples with purposive sampling technique. The instruments used were Semi Quantitative Food Frequency Questionnaire (SQ FFQ) questionnaire and Sedentary Behavior Questionnaire (SBQ). Chi-square test was used to analyze bivariate data. Results: The results showed that a high sedentary lifestyle was more prevalent in the case group (65.9%). Adequate energy intake was more in the control group (90.2%). Excess protein intake in the case group (83.0%). Adequate fat intake in the control group (92.7%). Adequate carbohydrate intake in the control group (95.1%). There was a relationship between sedentary lifestyle (p-value = 0.027), energy intake (p-value = 0.026), protein intake (p-value = 0.001), fat intake (p-value = 0.003) and carbohydrate intake (p-value = 0.007) with the nutritional status of housewives. Conclusions: There was a relationship between high sedentary lifestyle and eating habits with the nutritional status of housewives.